An engineered recombinant protein containing three structural domains in SARS-CoV-2 S2 protein has potential to act as a pan-human coronavirus entry inhibitor or vaccine antigen - Xinling Wang; Lujia Sun; Zezhong Liu; Lixiao Xing; Yun Zhu; Wei Xu; Shuai Xia; Lu Lu; Shibo Jiang (Emerging Microbes and Infections)
The threat to global health caused by three highly pathogenic human coronaviruses (HCoV), SARS-CoV-2, MERS-CoV and SARS-CoV, calls for the development of pan-HCoV therapeutics and vaccines. This study reports the design and engineering of a recombinant protein designated HR1LS. It contains three linked molecules, each consisting of three structural domains, including a heptad repeat 1 (HR1), a central helix (CH), and a stem helix (SH) region, in the S2 subunit of SARS-CoV-2 spike (S) protein. It was found that HR1LS protein automatically formed a trimer able to bind with heptad repeat 2 (HR2) region in the SARS-CoV-2 S2 subunit, thus potently inhibiting HCoV fusion and entry into host cells. Furthermore, immunization of mice with HR1LS, when combined with CF501 adjuvant, resulted in the production of neutralizing antibodies against infection of SARS-CoV-2 and its variants, as well as SARS-CoV, MERS-CoV, HCoV-229E, HCoV-NL63 and MjHKU4r-CoV-1. These results suggest that HR1LS is a promising candidate for further development as a novel HR1-trimer-based pan-HCoV entry inhibitor or vaccine for the treatment and prevention of infection by SARS-CoV-2 and its variants, but also other HCoVs with the potential to cause future emerging and re-emerging infectious coronavirus diseases.